5-bit Wallace-tree thermometer-to-binary encoders: 0.18µm CMOS technology flash ADCs comparing conventional CMOS and transmission gate CMOS full adder: article / Alia Aqilah Ahmad Termidhi - Ahmad Termidhi, Alia Aqilah (2012)
The thermometer-to-binary decoder becomes the constraint of the ultrahigh speed CMOS flash analog-to-digital. This paper present two different types of 5bit comparators will consumption [1]. Wallace-tree thermometer-to-binary encoders for ultra-high speed in flash ADC in 1.8V, 0.18µm CMOS technology. Two different types of Wallace-tree encoders are compared using different full adder which are Conventional CMOS full adder and Transmission Gate CMOS full adder. The study is carried out to compare the parameters in these two types Wallace-tree thermometer-to-binary encoders. The parameters studied are power consumption, number of transistors, and delay.